PENGARUH EARNING PER SHARE, DIVIDEND PER SHARE, DEBT TO EQUITY RATIO DAN CURRENT RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sultan Salahudin, 10.05.51.0065 (Students Journal of Economic and Management, 2015)
The objective of the study to examine the effect of EPS, DPS, DER and CR on stock prices in the manufacturing industry companies listed in Indonesia Stock Exchange . In this study using secondary data. The population used is the manufacturing companies listed in Indonesia Stock Exchange from 2009-2012. The sampling method study using purposive sampling technique. There are 45 companies studied . This study uses multiple regression analysis. These results indicate that only the variable EPS and DPS are positive and significant impact on stock prices, while the DER and CR variable and no significant negative effect on stock prices. Value Adjusted R Square of 0.898 ; which explains that the 89.8 % share price variable can be explained by the variable EPS, DPS, DER and CR while 10.2 % is explained by other variables outside the model . Keywords : Earning Per Share, Dividend Per Share, Debt to Equity Ratio, Current Ratio and stock prices